Genetics and epigenetics of arrhythmia and heart failure - Duygu, Burcu; Poels, Ella M.; Da Costa Martins, Paula A. (Frontiers in Genetics, 2013)
Heart failure (HF) is the end stage of several pathological cardiac conditions including myocardial infarction, cardiac hypertrophy and hypertension. Various molecular and cellular mechanisms are involved in the development of HF. At the molecular level, the onset of HF is associated with reprogramming of gene expression, including downregulation of the alpha-myosin heavy chain (α-MHC) gene and sarcoplasmic reticulum Ca2+ ATPase genes and reactivation of specific fetal cardiac genes such as atrial natriuretic factor (ANF) and brain natriuretic peptide (BNP). These deviations in gene expression result in structural and electrophysiological changes, which eventually progress to HF. Cardiac arrhythmia is caused by altered conduction properties of the heart, which may arise in response to ischemia, inflammation, fibrosis, aging or from genetic factors. Because changes in the gene transcription program may have crucial consequences as deteriorated cardiac function, understanding the molecular mechanisms involved in the process has become a priority in the field. In this context, various studies besides having identified different DNA methylation patterns in HF patients, have also focused on specific disease processes and their underlying mechanisms, also introducing new concepts such as epigenomics. This review highlights specific genetic mutations associated to the onset and progression of HF, also providing an introduction to epigenetic mechanisms such as histone modifications, DNA methylation and RNA-based modification, and highlights the relation between epigenetics, arrhythmogenesis and HF.